Dual-Mode Human-Robot Collaboration With Guaranteed Safety Using Time-Varying Zeroing Control Barrier Functions and Quadratic Program - Shi, Kaige; Hu, Guoqiang (IEEE robotics and automation letters, 2023)
Safety and efficiency are two important aspects of human-robot collaboration (HRC). Most existing control methods for HRC consider either contactless HRC or physical HRC, hindering more efficient HRC. The proposed control framework enables dual-mode HRC, filling the gap between contactless and physical HRCs. With the framework, the robot can perform contactless HRC under safety regulations regarding the co-working human. Meanwhile, the human can safely interrupt the robot via physical contact to enter physical HRC, in which he/she can hand guide the robot or take over its gripped object. First, human safety is defined as bounded approaching velocities between human and multiple robot links based on ISO/TS 15066, allowing gradual establishing of physical contact. Then, the time-varying zeroing control barrier function is proposed and defined to guarantee the bounded approaching velocities by a safety control set. Second, a unified task control set is designed to achieve different robot tasks for different HRC modes in a unified manner. The unified task control set enables the robot to switch smoothly between the two HRC modes. An optimal final control input is determined by a quadratic program based on different control sets. Experiments were conducted to verify the proposed framework and compare the proposed framework with existing methods. An application example is presented to show the versatility of the proposed framework.